GLOBAL POSTURAL REEDUCATION IN THE TREATMENT OF ADOLESCENT IDIOPATHIC SCOLIOSIS (Fiep Bulletin - online, 2014)
The conservative treatment with physiotherapy of adolescent scoliosis, has not proven to be effective in terms of lasting correction of curves. Global Postural Re-Education (RPG) is an innovative method of posture correction developed by Ph. Souchard. Although the method is widely used clinically for prevention and rehabilitation of musculoskeletal dysfunctions, the literature is still scarce and provide controversial results. The current study aims to evaluate the efficacy of RPG method in the treatment of adolescent idiopathic scoliosis. Forty nine children (aged 10 to 16 years old), with adolescent idiopathic scoliosis (Cobb angle between 10° and 25°), were treated in the Department of Physiotherapy and private practice for the period of 10 years. They were randomly divided into two treatment groups. The RPG group (n=26) performed muscle chain stretching, while the control group (n=23) performed conventional physiotherapy program, including symmetrical exercises for the trunk muscles, lower and upper limbs. Statistically significant differences in the clinical study were obtained in RPG group to reduce the following parameters: the Cobb angle, the distance from the vertical occiput line to the gluteal sulcus, scapular asymmetry and vertical deviation of the apex for scoliosis (p < 0.01). In control group these results have not improved significantly. A RPG treatment approach appears more effective than conventionally used physiotherapy program in the treatment of adolescent idiopathic scoliosis.
Keywords: adolescent idiopathic scoliosis; physiotherapy